Architecting Hybrid Donor–Acceptor Dendritic Nanosheets Based on Polyoxometalate and Porphyrin for High‐Yield Solar Water Purification. (22nd December 2021) - Zhou, Yue; Lu, Qichen; Liu, Qingda; Yang, Haozhou; Liu, Junli; Zhuang, Jing; Shi, Wenxiong; Wang, Xun
Abstract: Harvesting solar energy for saline and polluted water purification is a sustainable and affordable solution to alleviate the stress on water shortages. However, the water evaporation rate relies on high optical intensity and suffers from inadequate energy conversion. Herein, a novel hybrid donor–acceptor dendritic nanosheets (denoted as DNS) composed of phosphomolybdic acid (PMA) clusters and porphyrin ligands is reported. Experimental results and molecular dynamics simulations indicate that the PMA and porphyrin are oriented attachment and assembled into a stable nanostructure. Benefiting from the advantages of the unique structure and photosensitive components, the DNS exhibits high evaporation rate of 2.23 kg m ‐2 h ‐1 with 90.9% energy efficiency under 1 sun irradiation. It is noteworthy that the evaporation performance is upgraded by innovative technology, and even under 0.5 sun that is close to the natural sunlight intensity, the evaporation rate reaches up to 1.31 kg m ‐2 h ‐1, which exceeds that of the vast majority of the reported evaporators. Furthermore, this evaporator also displays excellent seawater desalination and wastewater decontamination based on photo‐thermal distillation, highlighting its potential application toward water purification. Abstract : A novel donor‐acceptor dendritic nanosheets with well‐ordered channels is synthesized by self‐assembly of phosphomolybdic acid clusters and porphyrin ligands. Experimental results and molecular dynamics simulations prove that the building blocks are oriented attachment and form the stable nanostructure. Benefiting from the advantages of the photosensitive components and unique structure, the material exhibits excellent performance in both seawater desalination and sewage purification.